Role Model-Based Character Education (Sayyidah Fatimah's Personality Values for the Millennial Generation of Women) - Fauziah, Fauziah; Asykurullah, Afton (Civiliza Publishing, Indonesia., 2025)
Character education is a fundamental aspect in shaping individual personality, especially for women, who play a crucial role in building civilization through their roles as primary educators within the family and as agents of change in society. This study aims to explore and analyze the relevance of Sayyidah Fatimah’s character values particularly resilience, emotional intelligence, and moral integrity in shaping contemporary character education for women. Using a library research method, the study collects and examines scholarly literature, historical sources, biographical accounts, and modern academic writings related to Islamic character development and female education. The analysis reveals that Sayyidah Fatimah’s exemplary qualities provide a comprehensive model for strengthening spiritual grounding, emotional stability, and social empathy among modern women. The findings indicate that integrating her values into character education can enhance women’s ability to navigate personal challenges, maintain ethical consistency, and develop emotional maturity, ultimately contributing to a more balanced, resilient, and value-oriented female identity in today’s dynamic social environment.